2005
DOI: 10.1088/0031-9155/50/15/005
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and microdosimetric study of contrast-enhanced radiotherapy with kilovolt x-rays

Abstract: Kilovolt x-rays are clearly suboptimal compared to MV photon beams for radiotherapy of deep-seated tumours because of the increased attenuation in tissue, causing a rapid dose fall-off. This picture could change drastically when tumours can be labelled with contrast medium, containing high atomic number elements. This causes a significant dose enhancement to the tumour by exploiting the high cross sections for the photo-electric effect for kV x-rays. In this work, we have investigated the dosimetric and microd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 22 publications
2
53
0
Order By: Relevance
“…32 It is widely accepted that the use of low-energy kilovoltage beams could maximize tumor dose enhancement; 33,34 however, their inherent shallow penetration and significant dose heterogeneity inside the target tumor hinder the translation of this technology to the clinic. 35 Compared with kilovoltage, the clinically relevant megavoltage X-ray energies have relatively limited application in the field of nanoparticle-based radiotherapy. In this study, we demonstrated the efficacies of AuNPs and AgNPs in conjunction with a single moderate dose of 6 MV radiation with the latter being the stronger.…”
mentioning
confidence: 99%
“…32 It is widely accepted that the use of low-energy kilovoltage beams could maximize tumor dose enhancement; 33,34 however, their inherent shallow penetration and significant dose heterogeneity inside the target tumor hinder the translation of this technology to the clinic. 35 Compared with kilovoltage, the clinically relevant megavoltage X-ray energies have relatively limited application in the field of nanoparticle-based radiotherapy. In this study, we demonstrated the efficacies of AuNPs and AgNPs in conjunction with a single moderate dose of 6 MV radiation with the latter being the stronger.…”
mentioning
confidence: 99%
“…In theory, loading high Z materials into the tumor could result in greater photoelectric absorption within the tumor than in surrounding tissues, and thereby enhance the dose delivered to a tumor during radiation therapy. At least 20 years ago, it was noted in vitro that this effect might be employed to enhance radiotherapy for cancer.(1) Accumulating studies have demonstrated the dose enhancement caused by high Z materials in kilovoltage beams (2)(3)(4) and in megavoltage beams.(5-8) Moreover, enhanced cell killing was also observed when cells were irradiated adjacent to high Z materials by kilovoltage X-rays. (9)(10)(11)(12) In clinical practice, electron beams from linear accelerators have increasingly taken the place of kilovoltage X-ray beams for skin and subcutaneous tumors because they offer distinct advantages in terms of dose uniformity in the target volume and in minimizing the dosage to deeper tissues.…”
mentioning
confidence: 99%
“…(1) Accumulating studies have demonstrated the dose enhancement caused by high Z materials in kilovoltage beams (2)(3)(4) and in megavoltage beams.…”
mentioning
confidence: 99%
See 2 more Smart Citations